Community Empowerment in the Preparation of Coastal Area Masterplans in Bontang Utara District: Pendampingan Penyusunan Masterplan Kawasan Pesisir di Kecamatan Bontang Utara - Utomo, Pandu K.; Sari, Dharwati P.; Nopianti, Putri; Tristanto, Kartika; Awinuwu M, Agel (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
The problem of slum settlements is one of the issues in the coastal areas of densely populated residential areas in Bontang City. The preparation of a masterplan for the coastal area of North Bontang District is very important to prevent the expansion of slum areas in this district. This community service activity was carried out to assist policy makers in the preparation of the master plan. The PkM team provided assistance in the preparation of this master plan by providing insights and knowledge according to the competencies of the team members. Stakeholder involvement was very significant in this activity. The results of this mentoring activity were a very high level of participation and produced a master plan report that strongly supports the Bontang City Government program.